Formation of PCDD/Fs from Oxidation of 2-Monochlorophenol over an Fe(2)O(3)/Silica Surface - Nganai, Shadrack (2012)
The role of iron in surface-mediated formation of polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs) from 2-chlorophenol (2-MCP) was investigated over the temperature range of 200 to 550°C under oxidative conditions. In order to compare and contrast with previous work on copper and ferric oxide-mediated pyrolysis of 2-MCP, identical reaction conditions were maintained (50 ppm 2-MCP, model fly-ash particles containing 5% Fe(2)O(3) on silica). Observed products included dibenzo-p-dioxin (DD), 1-monochlorodibenzo-p-dioxin (1-MCDD), dibenzofuran (DF), 4,6-dichlorodibenzofuran (4,6-DCDF), 2,4– and 2,6-dichlorophenol, 2,4,6-trichlorophenol, quinone, catechol, chloro-o-quinone, chlorocatechol and polychlorinated benzenes. Yields of DD and 1-MCDD were 2 and 5 times higher than under pyolysis conditions, respectively. Although 4,6-DCDF was the major PCDD/F product formed with a yield that was 2.5x greater than under pyrolysis, the yield of non-chlorinated DF, which was the dominant PCDD/F product under pyrolysis, decreased by a factor of 3. Furthermore, the ~2x higher yield of PCDDs under oxidative conditions resulted in a PCDD to PCDF ratio of 0.75 compared to a relatively low ratio of 0.39 previously observed under pyrolytic conditions.